Antikeratin antibodies: diagnostic and prognostic markers for early rheumatoid arthritis. Issue 6 (June 1992) - Paimela, L; Gripenberg, M; Kurki, P; Leirisalo-Repo, M
Abstract : Antibodies to the stratum corneum of rat oesophagus (antikeratin antibodies) were assayed by indirect immunofluorescence in a prospective study of patients with early rheumatoid arthritis (RA). At the beginning of the study, antikeratin antibodies of IgG class were detected in serum samples from 27/71 (38%) patients compared with 1/20 (5%) control patients with reactive arthritis, and 1/38 (3%) healthy blood donors. At the end of the two year follow up, 27/67 (40%) patients with RA were positive for antikeratin antibodies. The patients with RA who were initially positive for antikeratin antibodies had a more active disease course than the patients negative for antikeratin antibodies as measured by clinical, laboratory, and radiological variables. The prevalence of positivity for antikeratin antibodies fluctuated during the follow up, the variation paralleling the disease activity. The occurrence of HLA-DR4 was similar in patients with RA who were positive and negative for antikeratin antibodies. Antikeratin antibodies were also found in seronegative patients with RA, confirming that antikeratin antibodies do not have rheumatoid factor activity. These results show that antikeratin antibodies are detectable at the time of the initial diagnosis of RA and that the positivity for antikeratin antibodies may have prognostic significance in early RA.